EKSISTENSI PAGUYUBAN ANGKLUNG MOTEKAR DI MALIOBORO YOGYAKARTA - HANIFAH NUR MEHTA (Saraswati)
Angklung motekar community has formed at the beginning of 2005 until now. The members angklung motekar community the majority come from Cilacap. Angklung motekar community exist its existency from beginning until now its with show work profesionality, creativity, backed up with human resources who have ability in his position and has unique characteristic to carries on “dangdut koplo” song at its performance. This community makes a song with simple arransement, because they have learned a music otodidac. Angklung motekar community always exists its unique characteristic of music and its performance on the stage are the evidence belong angklung motekar community.   Keywords : Existency, Creativity, Arransement.